Comportamiento de mezcla de concreto cemento Portland con adiciones de 5 y 10% de cenizas de lodos (2019)
In the present study the sludge ashes coming from water treatment operations of the treatment plant of Triple A company, in Barranquilla city are analyzed. These analyzes are intended to determine the usefulness of sludge as a hydraulic binder, creating an ecological arrangement of thereof, and helping to minimize the extractive activities of raw materials used in the construction industry. Specimens were manufactured with a 5% and 10% replacement of cement by sludge ashes and a control mixture that required a theoretical compression strength of 4000 Psi (28 MPa) to be compared with the results and behavior of the modified concrete. The results from this study showed that sludge ashes from the water treatment can be replaced in small percentages with the Portland cement in concrete mixture without negatively affecting the compressive strength. It was obtained that the specimens tested for compression reach 3000 psi, which corresponds to a concrete of moderate resistance, which meets the requirements to be used in the construction of buildings of small housing type and simple buildings.